HUBUNGAN MINAT MASUK SEKOLAH KEJURUAN DENGAN HASIL BELAJAR MATA PELAJARAN GAMBAR TEKNIK JURUSAN TEKNIK GAMBAR BANGUNAN KELAS XI SMK N 1 SUMATERA BARAT TAHUN AJARAN 2017/2018 - 2135-5140, Mitasari (Universitas Negeri Padang, 2018)
Abstract—. The aims of this research is to find a relationship beetwen the intersesting to enter SMK N 1 West Sumatera and activemant result on Engginering Drawingfor academic year 2017/2018 at grade XI SMK N 1 West Sumatra. Member of sampling is 47 students that taken from total sampling technique. Data analysis techniques used are: 1) Descriptive analysis, 2) normality test and linearity test, and 3) Hypothesis Test. The results of this study is that there is a significant relationship between intersesting to enter SMK N 1 West Sumatera and activemant result on Engginering Drawingfor academic year 2017/2018 at grade XI SMK N 1 West Sumatra, with 95% confidence level. This can be seen from the correlation coefficient value of 0.510, it is mean that the category of relationship is enough ( between 0,40-0,70). Keywords: Student Perception, Learning Result, Engginering Drawing